Analisis Transaksi Akad Salam Dalam Jual Beli Online - ramahdani, ririn (IAIN Parepare, 2024)
Analysis of salam contract transactions in online buying and selling with a focus on the salam contract scheme, fulfillment of pillars and legal requirements in fiqh law, as well as ease of salam contract transaction mechanisms in e-commerce. The research method used is descriptive qualitative, with data analysis techniques that include data reduction, data presentation and drawing conclusions. Primary and secondary data sources were used in this research, including verses from the Koran, hadith, and related books. The findings of this article provide a deeper understanding of salam contract transactions in the context of online buying and selling, as well as the potential of the e-commerce market in Indonesia.